HUBUNGAN KOMUNIKASI INSTRUKSIONAL DENGAN HASIL BELAJAR ILMU UKUR TANAH DI SMK NEGERI 1 JAKARTA - Agung Arianto; Tuti Iriani; Riyan Arthur (LPPM Universitas Negeri Jakarta, 2019)
This study aims to determine the correlation between teacher’s instructional communication and learning outcomes in the form of final exam in the subjects of Class X Land Measurement Science expertise in Modeling and Building Information expertise program at SMKN 1 Jakarta. The type of research used in this study is associative quantitative research. The method used is a survey method with a correlational approach. The population in this study were class X students of the Permodean Design and Building Information program at SMK 1 Jakarta, as many as 102 people. The sample in this study used the Random Sampling technique which was tested on 80 students. The results showed that there was a positive and significant relationship between instructional communication and learning outcomes as evidenced by: correlation coefficient value of 0.601 which is included in the category of strong relationships, the significance value of the correlation coefficient t count = 6.851 and t table = 1.991 which indicates a significant relationship, and the relationship between instructional communication and final exam learning outcomes is obtained by the determination coefficient value of 0.376. So the instructional communication factor can influence learning outcomes, which is 37.6%, and the rest is influenced by other factors beyond instructional communication skills.